Evaluation of Different Land Preparation Techniques for Preparing Medium Textured Soil in Rice Production under Agro-Ecological Conditions of Sheikhupura-Pakistan - Usman Hassan; Muhammad Shahbaz; Muhammad Saleem Kashif; Liaqat Ali; Muhammd Tariq Chaudhary; Wardah Qamar (Turkish Journal of Agriculture: Food Science and Technology)
Tillage is an important factor affecting different soil properties and crop yields. Tillage relates to applying forces to soil using different implements for preparation of a proper seed bed. For rice crop, land preparation is a rigorous and time consuming operation that needs special attention for preparing a puddled soil condition to transplant the weak and tender rice seedlings. A field experiment was established under agro-ecological conditions of Sheikhupura to evaluate different land preparation techniques during fall in 2017 and 2018 years. The experiment was performed at Adaptive Research Farm Sheikhupura. It was laid out in randomized complete block design (RCBD) with four different land preparation techniques including T1= Cultivator (4 times) + Planking (2 times) (Farmer’s Practice), T2=MB plough (1 time) + Disc Harrow (1 time) + Planking (2 Times), T3=MB plough (1 time) + Cultivator (2 times) + Planking (2 Times) and T4= Rotavator (1 time) + Disc Harrow (1 time) + Planking (2 Times), each treatment replicated thrice during both the years. All the other agronomic and crop husbandry operations were kept uniform throughout the growing season every year. The results revealed that preparing land with MB plough (1 time), Disc Harrow (1 time) and Planking (2 times) is the best land preparation method can increase the paddy yield 13.5-17.5% as compared to the traditional method practised by the farmers. Moreover, highest plant height (134.00 cm and 132.00 cm), number of tillers (224 and 220 m-2), number of grains per spike (130 and 116) and 1000-grain weight (23.0 and 22.0 g) respectively during Kharif-18 and Kharif-19 was also recorded in the same treatment. So, preparation of land for paddy in agro-ecological conditions of Sheikhupura using MB plough (1 time), Disc Harrow (1 time) and Planking (2 times) can significantly enhance the paddy yield.